2009
DOI: 10.1162/qjec.2009.124.3.969
|View full text |Cite
|
Sign up to set email alerts
|

E-ZTAX: Tax Salience and Tax Rates*

Abstract: This paper tests the hypothesis that the salience of a tax system affects equilibrium tax rates.To do this, I analyze how toll rates change after toll facilities adopt electronic toll collection. Unlike manual toll collection, in which the driver must hand over cash at the toll collection plaza, electronic toll collection automatically debits the toll amount as the car drives through the toll plaza, thereby plausibly decreasing the salience of the toll. I find robust evidence that toll rates increase following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
129
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(148 citation statements)
references
References 24 publications
15
129
0
Order By: Relevance
“…Yet, there are indications that consumers are more sensitive to discrete price increases, such as tax breaks for cars that meet specific criteria (see e.g. Finkelstein 2009;Klier and Linn 2015;Kok 2013). This study did not explicitly model these elements of tax design.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there are indications that consumers are more sensitive to discrete price increases, such as tax breaks for cars that meet specific criteria (see e.g. Finkelstein 2009;Klier and Linn 2015;Kok 2013). This study did not explicitly model these elements of tax design.…”
Section: Discussionmentioning
confidence: 99%
“…6 Finally, our work is distinct from previous research that has found that the salience of a government policy can alter its effects. For instance, Chetty et al (2009) show that posting sales-tax inclusive prices lead people to respond to the taxinclusive price, and Finkelstein (2009) shows that drivers who receive a monthly bill for tolls (EZ Pass) have worse recall of the toll amount. 7 In our experiment, the policy and its associated monetary incentives (a fine or tax for not purchasing insurance) are equally salient in both conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Congdon et al 2009, Dell'Anno andDe Rosa, 2013) and concept of Tax Salience (e.g. Chetty et al 2009, Finkelstein 2009). Schneider and Enste (2000) present a comprehensive survey about the shadow economy, also including different measurement methodologies, which we do not discuss here.…”
Section: Fiscal Illusion and The Shadow Economymentioning
confidence: 99%